(untitled) (Scientia Agricola, 2015)
Growth regulators are used in the production of apples worldwide, especially to extend the harvest period and maintain postharvest quality. This study aimed to investigate the effects of applying aminoethoxyvinylglycine (AVG) in isolation as well as in combination with other growth regulators and postharvest techniques on the harvest quality and storage potential of ‘Brookfield’ apples (Malus domestica), a ‘Gala’ strain. Fruit receiving AVG only had the highest starch content and the highest titratable acidity at harvest. After 8 months of storage, the AVG + 1-MCP (1-methylcyclopropene) and AVG + ABS (ethylene absorption) conserved higher flesh firmness than to all the other treatments. Naphthaleneacetic acid (NAA) application induced ACC oxidase enzyme activity at harvest, but not after storage. AVG application, with or without the aid of another technique, did not decrease the red skin color of ‘Brookfield’ apples. Low mealiness and a high healthy fruit percentage was obtained when the fruits were submitted to pre-harvest AVG application combined with NAA, 1-MCP and ABS. Internal carbon dioxide had an inverse correlation with the quantity of healthy fruit and was directly correlated with mealiness.